THE EFFECT OF LEADERSHIP STYLE OF THE PRINCIPAL ON THE PERFORMANCE SECONDARY SCHOOL - Manish kumar (International Journal of Multidisciplinary Research and Studies, 2021)
Many different firms have been forced to adopt a strategy of constant direction, modification, and flexibility as a result of the chaotic and unpredictable environment change. Leadership that is both effective and dedicated is essential during these times of change in order to successfully steer the company through the difficult transitions that are ahead (Gunawardena, 2015). Leaders construct systems of incentive to elicit the greatest possible performance from their employees and to assist them in finding candidates for employment (Jay, 2014). In recent years, education has also undergone fundamental changes in terms of breadth and variety. This transformation has occurred concurrently with the remarkable development that has occurred as a result of the dynamic change process. Education at elementary and secondary levels becomes a pivotal centre for the growth of a society in terms of acquiring the necessary knowledge and abilities. As a result, the performance of instructors in schools is critical to the education of students, the spread of information, the outcome, and many other elements. Through strong leadership, the principal is responsible for ensuring that the teachers fulfil their professional responsibilities. One way to explain the significant impact that school principals have is to point out that they receive training to be able to utilise the myriad of methods that are included in the schools' administrative processes (Alagheband, 1997).